Characterization of plasmid‐mediated AmpC‐producing E. coli from Swedish broilers and association with human clinical isolates. (12th April 2013) - Börjesson, S.; Jernberg, C.; Brolund, A.; Edquist, P.; Finn, M.; Landén, A.; Olsson‐Liljequist, B.; Tegmark Wisell, K.; Bengtsson, B.; Englund, S.; Pappas, G.
Abstract A selection of plasmid‐mediated AmpC‐producing Escherichia coli isolates carrying blaCMY‐2 from Swedish broilers were characterized to establish their relatedness to and a possible overlap with human clinical E. coli isolates. The results showed diversity among the E. coli isolated from broilers, indicating that the spread in the population was not due to one strain. However, only one type of plasmid belonging to replicon type incK was identified. Furthermore, there were no indications of spread of blaCMY‐2E. coli isolates from broilers to human clinical settings, although Swedish broilers may be a source of blaCMY‐2 and/or the plasmid carrying blaCMY‐2.